1983
DOI: 10.1103/physrevb.27.7827
|View full text |Cite
|
Sign up to set email alerts
|

Bipolarons in polypyrrole chains

Abstract: First-principles calculations on the geometric and electronic structures of undoped and doped polypyrrole chains indicate the appearance upon high doping of bipolaron states in the gap. A picture of the band-structure evolution upon doping is presented, showing the presence of bipolaron bands in the gap for experimentally achieved doping levels. A conductivity mechanism based on motion of spinless bipolarons is consistent with the absence of ESR signal in electrochemically cycled highly conducting polypyrrole.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
1
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(171 citation statements)
references
References 19 publications
6
163
1
1
Order By: Relevance
“…As previously pointed out based on theoretical calculations, the respective differences between the LUMO and the lower, binding bipolaron (dication) state and the HOMO as well as between the upper, antibonding bipolaron state are fairly similar to the respective differences found for the polaron (cation radical) state [39,40]. Experimental observations were in slight disagreement.…”
Section: In Situ Uv-vis Spectroelectrochemistrysupporting
confidence: 51%
“…As previously pointed out based on theoretical calculations, the respective differences between the LUMO and the lower, binding bipolaron (dication) state and the HOMO as well as between the upper, antibonding bipolaron state are fairly similar to the respective differences found for the polaron (cation radical) state [39,40]. Experimental observations were in slight disagreement.…”
Section: In Situ Uv-vis Spectroelectrochemistrysupporting
confidence: 51%
“…Figures 5 and 6 show nonresonant and resonant C K x-ray emission spectra of undoped PANi and the doped phases measured with the excitation energies of 302.2 and 285.0 eV. By comparing the observed emission spectra with molecular orbital calculations 21 and band-structure calculations, 27 three major bands ͑labeled A-C͒ can be identified in the spectra. Peak A corresponds to -like states, peak B is due to both and contributions, with dominating, while peak C is due only to electronic states.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a comparison of their work with experimental results, they concluded that the most probable structure of PPP is nearly planar with an inter-ring torsional angle of less than 20°. Some of the earliest band structure calculations for PPP were performed by Brédas et al [27][28][29][30] They used the experimental values of the geometrical parameters and the torsional angle as input for HF calculations on an alternately tilted chain. Bakhshi and Ladik 31 made an HF calculation of the ionization energy, electron affinity, and bandwidth values for both a planar and a helical PPP chain.…”
Section: Introductionmentioning
confidence: 99%